1999
DOI: 10.1086/515071
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Prophylaxis Using Azithromycin: A Double‐Blind, Placebo‐Controlled Trial in Irian Jaya, Indonesia

Abstract: New drugs are needed for preventing drug-resistant Plasmodium falciparum malaria. The prophylactic efficacy of azithromycin against P. falciparum in malaria-immune Kenyans was 83%. We conducted a double-blind, placebo-controlled trial to determine the prophylactic efficacy of azithromycin against multidrug-resistant P. falciparum malaria and chloroquine-resistant Plasmodium vivax malaria in Indonesian adults with limited immunity. After radical cure therapy, 300 randomized subjects received azithromycin (148 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(67 citation statements)
references
References 26 publications
0
66
0
1
Order By: Relevance
“…This double-blind, placebo-controlled trial assessed the prophylactic efficacy and tolerability of azithromycin in men and women who had been radically cured (with concurrent quinine doxycycline and primaquine) of any preexisting malaria infection. Details of the study have been reported previously (21). Three hundred Indonesian adults (225 soldiers and 75 villagers) received either (i) azithromycin (750-mg loading dose followed by 250 mg/day) plus a doxycycline placebo (n ϭ 148) (arm A), (ii) doxycycline (100 mg/day) plus an azithromycin placebo (n ϭ 75) (arm D), or (iii) a double placebo (n ϭ 77) (arm P).…”
Section: Methodsmentioning
confidence: 99%
“…This double-blind, placebo-controlled trial assessed the prophylactic efficacy and tolerability of azithromycin in men and women who had been radically cured (with concurrent quinine doxycycline and primaquine) of any preexisting malaria infection. Details of the study have been reported previously (21). Three hundred Indonesian adults (225 soldiers and 75 villagers) received either (i) azithromycin (750-mg loading dose followed by 250 mg/day) plus a doxycycline placebo (n ϭ 148) (arm A), (ii) doxycycline (100 mg/day) plus an azithromycin placebo (n ϭ 75) (arm D), or (iii) a double placebo (n ϭ 77) (arm P).…”
Section: Methodsmentioning
confidence: 99%
“…Blood blots were collected from participants in a clinical trial 30 assessing the prophylactic efficacy of azithromycin that was also conducted in Arso PIR V and surrounding villages from July 1996 to January 1997. After radical cure therapy (quinine, 10 mg/kg twice a day for 4 days, doxycycline, 100 mg twice a day for 10 days, primaquine base, 30 mg a day for 14 days) participants were randomized to receive azithromycin, doxycycline, or placebo.…”
Section: Methodsmentioning
confidence: 99%
“…Attack rates for malaria in the Arso region have typically ranged between 0 . 5 and 4 infections/person-year [32][33][34][35]. Cross-sectional studies in similar villages revealed relatively uniform prevalence of parasitemia across age groups during the first year of exposure [20].…”
Section: Study Sitementioning
confidence: 99%